Russia-Japan Security Dialogue - O. G. Paramonov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
In the face of deteriorating the regional security environment in East Asia, a noticeable growth of Japan’s defense capabilities and Tokyo’s departure from most self-restraints in the field of security policy look quite expected and natural process. At the same time, Japan continues to rely on the alliance with the United States. On the other hand, relations between Washington and Moscow are now at their lowest point since the Cold War. Japan itself has territorial claims to Russia. This means, based on confrontational logic that returns to the international agenda, that Japan’s traditionally reserved attitude towards Russia should be maintained. However, today we are witnessing a different situation. After the start of regular personal meetings between Russian President Vladimir Putin and Japanese Prime Minister Shinzo Abe, the dialogue is intensified on a wide range of issues, including those related to international security, and especially its regional aspect. Although certain background for that was noted before the Sochi meeting between V. Putin and S. Abe, this foreign policy turn, and, in particular, its speed, came as a surprise not only for Tokyo’s Western partners, but also for many Japanese politicians and experts. This article is devoted to the analysis of its possible causes, as well as the search for an answer to the next question.Is the dialogue between Russia and Japan a situational political maneuver or a step towards cooperation on security issues?